South African parents’ views on oral, signing, and bilingual communication for Deaf or hard-of-hearing children - Katijah Khoza-Shangase; Jasmine Bent (African Journal of Disability)
Background: Parents of Deaf or hard-of-hearing (DHH) children are faced with a plethora of overwhelming decisions concerning their children, particularly during the early stages of development. Among these decisions are those concerning assistive devices and the modes of communication for their child.